Quality characteristics and antioxidant activities of goat milk yogurt with added jujube pulp. (30th March 2019) - Feng, Cuijiao; Wang, Bini; Zhao, Aiqing; Wei, Lusha; Shao, Yuyu; Wang, Yin; Cao, Binyun; Zhang, Fuxin
Highlights: Goat milk yogurt (GMY) has a goaty flavor restricting its acceptability and development. Added jujube pulp can effectively improve the flavor and the health benefits of the final GMY product. YJ3 exhibited the desirable overall quality characteristics including the sensory acceptance. Abstract: This study aimed to evaluate the effects of the added jujube pulp on the quality characteristics and antioxidant activities of goat milk yogurt (GMY) during 28 days of refrigerated storage. Four GMY formulations were prepared, each varying in the added jujube pulp amount (Y0: not containing jujube pulp; YJ3, YJ6, YJ9: containing 3, 6, 9 g of jujube pulp per 100 g GMY, respectively). There was no significant differences in the viable counts, pH values and titratable acidities of all formulations during the storage. All formulations showed the viable counts all above 10 6  CFU/mL over the assessed storage period. However, YJ3 exhibited the desirable hardness, adhesiveness and water holding capacity. Moreover, the addition of jujube pulp weakened greatly the goaty flavor, improving the sensory acceptance, and increased the antioxidant activities of GMY. Therefore, GMY containing jujube pulp is optional for developing a novel goat dairy product with high added values.